ANALYSIS OF THE POTENTIAL INCOME OF TOBACCO (Nicotiana tabacum L.) FARMERS IN LIMAPULUH KOTA REGENCY OF WEST SUMATERA PROVINCE - Latifa, Dara; Ispinimiartriani, Ispinimiartriani; Soemarsono, Soemarsono; Syakib Sidqi, M. (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
West Sumatra is one of the tobacco producing provinces in Indonesia and the largest producer is Limapuluh Kota Regency. The majority of the population of Limapuluh Kota Regency livelihoods as farmers and one of them is tobacco farmers. The profession of tobacco farmers is often a seasonal profession for the community. Because the price, production and area of tobacco land are fluctuating. This research aims to find out the potential of tobacco farming to farmers' incomes in terms of income when compared to UMP West Sumatra, business feasibility, minimum land area and price. Research methods are survey using questionnaire instruments. The data used is primary and secondary data. Data analysis methods use income analysis, Z test comparison analysis, feasibility analysis, minimum land area and price. The results showed that the analysis of wet and dry tobacco farm income has the potential to provide benefits for farmers indicated by the value of the R/C feasibility analysis > 1. Comparative analysis with UMP West Sumatra using Test Z showed if the H1 hypothesis was accepted. Analysis of land area and minimum selling price shows that land area and price level appropriate to achieve income level in accordance with UMP West Sumatra.